Making research matter more - Levin, Ben (Education Policy Analysis Archives, 2004)
Interest in strengthening the impact and value of education research has been growing around the world. Here I outline a view of the nature of “impact” and point to instances where research has had a positive impact in education, but always within a larger social and political framework. A three element “model” of research impact is developed and used as the basis to assess current situations and to suggest steps that could be taken to support a fuller contribution to education and learning from research.